2015
DOI: 10.1161/circulationaha.114.014796
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes Mellitus on Hospitalization for Heart Failure, Cardiovascular Events, and Death

Abstract: Background-Despite the known association of diabetes mellitus with cardiovascular events, there are few contemporary data on the long-term outcomes from international cohorts of patients with diabetes mellitus. We sought to describe cardiovascular outcomes at 4 years and to identify predictors of these events in patients with diabetes mellitus. Methods and Results-The Reduction of Atherothrombosis for Continued Health (REACH) registry is an international registry of patients at high risk of atherothrombosis or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
135
1
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 427 publications
(149 citation statements)
references
References 37 publications
(39 reference statements)
1
135
1
12
Order By: Relevance
“…The prevalence of DM in patients with heart failure (HF) is extremely high (occurring in up to 40–45% of these patients) 7, 8. Not surprisingly, the burden of morbidity and mortality associated with CHF and DM represents, to date, a major challenge for the prospective sustainability of contemporary healthcare systems 8, 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of DM in patients with heart failure (HF) is extremely high (occurring in up to 40–45% of these patients) 7, 8. Not surprisingly, the burden of morbidity and mortality associated with CHF and DM represents, to date, a major challenge for the prospective sustainability of contemporary healthcare systems 8, 9, 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…19 Results from a landmark study by Nichols et al 20 demonstrated an increased HF risk for participants with versus without T2DM across all age groups studied, with an inverse association between age and magnitude of incremental HF risk, ranging from an 11-fold increased HF risk in the youngest age group <45 years, to a 2. 8 21 in which patients with versus without T2DM had a 33% greater incidence of hHF (9.4% versus 5.9%; adjusted hazard ratio [HR], 1.33; 95% confidence interval [CI], 1.18-1.50). Both the incidence of hHF and its incremental risk associated with T2DM observed in the REACH registry are of similar magnitude as for the outcome of cardiovascular death in the same study (8.9% versus 6.0% in participants with versus without T2DM; adjusted HR, 1.38; 95% CI, 1.26-1.52).…”
Section: Epidemiological Underpinningsmentioning
confidence: 99%
“…In patients with T2DM in the REACH registry, those with versus without HF at baseline had increased risk for cardiovascular death (adjusted HR, 2.45; 95% CI, 2.17-2.77) and hHF (adjusted odds ratio, 4.72; 95% CI, 4.22-5.29). 21 In subgroups of patients with T2DM enrolled into RCTs, such as the Losartan Intervention for End Point Reduction in Hypertension Study (LIFE) or the Reduction of End Points in Noninsulin-Dependent Diabetes Mellitus With the Angiotensin II Antagonist Losartan (RENAAL) trials, HF at baseline was associated with up to 12× higher death rates than T2DM individuals without baseline HF. 24,25 Furthermore, the composite of hHF and cardiovascular death occurred 75% more often in patients with versus without T2DM (28.5% of the cohort) in the Candesartan in Heart failure Assessment of Reduction in Mortality and Morbidity (CHARM) trials program (7599 patients with HF with up to 3.5 years of follow-up), irrespective of whether HF was caused by ischemic heart disease.…”
Section: Epidemiological Underpinningsmentioning
confidence: 99%
“…6 Although in general their risk of adverse cardiac events is lower than that of patients with T2D and CVD, this population remains at substantial lifetime risk of future ischemic events. 7 Furthermore, cardiovascular events that may not be directly mediated by ischemia, such as heart failure, are also important and occur in patients with and without established CVD. 7 In an analysis of the global REACH registry (Reduction of Atherothrombosis for Continued Health) of ≈20 000 patients with T2D, 1 of 20 patients with T2D and only risk factors for atherosclerosis were hospitalized with heart failure over 4 years of follow-up.…”
mentioning
confidence: 99%
“…7 Furthermore, cardiovascular events that may not be directly mediated by ischemia, such as heart failure, are also important and occur in patients with and without established CVD. 7 In an analysis of the global REACH registry (Reduction of Atherothrombosis for Continued Health) of ≈20 000 patients with T2D, 1 of 20 patients with T2D and only risk factors for atherosclerosis were hospitalized with heart failure over 4 years of follow-up. Furthermore, there is substantial heterogeneity of risk in patients with T2D without known CVD.…”
mentioning
confidence: 99%